Effect of Microfinance Practices on Growth of the Bodaboda Industry in Kenya; A Case of Kamukunji Sub-County - Njuguna, Joseph Mwangi; Njagi, Gilbert Nyaga (Journal of Business Management and Economic Development, 2023)
This research project aimed to analyze the effect caused by microfinance practices on the growth of the Boda Boda industry in Kenya (a case of the Kamukunji sub-county). A sample size of 150 out of 750 Boda boda riders of the target population in the Kamukunji sub-County, served as the basis for this study. The researcher used a descriptive study design with both qualitative and quantitative research methods being used. Questionnaires were used in data collection. The data was analyzed using statistical techniques such as regression analysis and descriptive statistics. Data was presented using bar graphs, pie charts, and tables to aid in effectively analyzing the results using SPSS software at 95% confidence level. Data was analyzed using tables and simple percentages for easy statistical inference; the hypothesis was tested using multivariate regression analysis. Findings from the study revealed that the interaction between loan accessibility, motorcycle ownership, microfinance training, and savings has surfaced as pivotal elements intricately interwoven into the fabric of industry expansion and empowerment specifically multiple regression results indicated that 91.9 percent of changes in growth are predicted by microfinance practices variables under study giving and the remaining percentage goes by other factors that are not in this study. Some of the recommendations drawn from the study are to enhance training initiatives, champion financial inclusion, foster motorcycle ownership and embrace microfinance education.